Agrarian Transformation, Land Reforms and Challenges to Development - Roy, Debal K Singha (The Eastern Anthropologist, 2024)
Against the backdrop of transition of agrarian society of India from colonialism to post colonialism and thereafter to post neoliberalism this paper endeavours to explin the broad processes of transition in the agrarian social structure in India as has ta
Keywords: Agrarian Question; Land Reform; Operation Barga; Peoples Movements; Capitalism